The French National Assembly elections of 1978 - Penniman, Howard Rae. (Washington, D.C. : American Enterprise Institute for Public Policy Research, 1980)
The French National Assembly Elections of 1978 is the second study of a French election published by the American Enterprise Institute (AEI). Both this volume and the earlier analyze the 1974 presidential election.
Includes bibliographical references and index.
ne 23/01/2019
Loans
Keywords: Elections; France